THE REPRESENTATION OF SOCIAL ACTOR STRATEGIES ENFOLDED IN AUSTRALIAN NEWSPAPER - Ribut - Surjowati; Roely - Ardianyah; Sugeng - Susiloadi; Siti - Azizah (PAROLE: Journal of Linguistics and Education, 2022)
The purposes of this research are to explain how and why Sydney Morning Herald communicates its ideologies in such a way through the social actors represented in news reports. The data collected were analyzed by using Fairclough’s and Van Dijk’s model of Critical Discourse analysis (CDA) and Theo Van Leeuwen’s framework of the representation of social actors. The findings show that the newspaper viewed the Out group social actors which were Indonesian government, Indonesian army and Indonesian military officers and In Group social actors which were Australian, Papuan activists and those who support Papuan conflict, in terms of assimilation, nomination and categorization, functionalization and identification, Impersonalization. These categorizations serve different purposes. Those which are related to the Out groups express a purpose to emphasize their brutality, superiority and dominance towards the indigenous Papuans. However, In Groups social actors were indicated as peace makers. These findings illustrate Australia’s political ideologies and hidden agenda for Indonesia. Australia is liberal country which respects individual freedom; therefore, government must protect and get justice. That is why, it is also became Australia’s responsibility to give aids to Papuans who is seeking better place as stated in the international law. Furthermore, Australia’s attitudes in trying to interference the conflict by providing a place for the Papuan asylum seekers is a picture of how this country is concerned towards Indonesia